2020
DOI: 10.3389/fneur.2020.598496
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Observational Registry of Repository Corticotropin Injection (Acthar® Gel) for the Treatment of Multiple Sclerosis Relapse

Abstract: Background and Purpose: Effective relapse treatment is critical for minimizing disability in patients with multiple sclerosis (MS). Repository corticotropin injection (RCI; Acthar® Gel) has demonstrated efficacy for the treatment of MS exacerbations. However, there is limited real-world evidence available regarding the relationship between the use of RCI for MS relapses and patient demographics, disease characteristics, and dosing regimens. In this multicenter, prospective, observational registry, patients rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…30 Baseline patient distribution by EDSS state and relapse severity were derived from the MS Relapse Registry, titled "Observational Registry of Acthar Gel for Participants with Multiple Sclerosis Relapse," funded by Mallinckrodt Pharmaceuticals (N = 125; Table 1). 17,31 The study was conducted to monitor the course of MS and to document relapses and the recovery process, in a group of MS patients treated with RCI.…”
Section: Model Inputs Clinical Probabilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Baseline patient distribution by EDSS state and relapse severity were derived from the MS Relapse Registry, titled "Observational Registry of Acthar Gel for Participants with Multiple Sclerosis Relapse," funded by Mallinckrodt Pharmaceuticals (N = 125; Table 1). 17,31 The study was conducted to monitor the course of MS and to document relapses and the recovery process, in a group of MS patients treated with RCI.…”
Section: Model Inputs Clinical Probabilitiesmentioning
confidence: 99%
“…7,16 Further, clinically meaningful improvements in MS Impact Scale 29 item version 1 (MSIS-29v1) physical subscale were observed in a prospective observational study of patients with treatment-refractory MS on RCI. 17 Statistically significant improvements in clinician-rated scales (Expanded Disability Status Scale [EDSS] and Clinical Global Impression of Improvement [CGI-I]) were also observed. 17 A retrospective claims analysis comparing RCI and alternative therapies supported the effectiveness of RCI in reducing relapses in MS. 8,18 Further, a recent literature review corroborates the efficacy of RCI in MS. 16 Initial economic analyses indicated that RCI was costsaving compared to PMP or IVIg in resolving MS relapses from a payer perspective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repository corticotropin injection (RCI; Acthar ® Gel, Mallinckrodt Pharmaceuticals, Hampton, NJ, USA) is a naturally sourced complex mixture of adrenocorticotropic hormone (ACTH) analogs and other pituitary peptides. 7 RCI is currently approved by the US Food and Drug Administration (FDA) for treatment of exacerbations of MS. 7 RCI is anti‐inflammatory by stimulating endogenous corticosteroid production and can exert additional immunomodulatory effects by binding to melanocortin receptors (MCRs) on immune cells. 8 , 9 , 10 Notably, in vitro studies have shown that RCI elicits distinct functional activity at MCRs from that of synthetic MCR agonists.…”
Section: Introductionmentioning
confidence: 99%
“…RCI is approved by the US Food and Drug Administration for the treatment of severe acute and chronic allergic and inflammatory processes involving the eye and its adnexa, including keratitis [7]. RCI has also been found effective for the treatment of persistently active systemic inflammatory disorders that have not responded to corticosteroids and other standard-of-care therapies [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%